1976
DOI: 10.2466/pr0.1976.38.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in Performance of Free-Operant Avoidance Behavior of Rats

Abstract: Possible daily periodicity in experiments involving conditioned behaviors has not usually been investigated or controlled. The present experiment argues for such studies in that variation in the performance of a free-operant avoidance task by 30 rats was detected as a function of when during the 24-hr. day behavioral testing occurred. In terms of shocks avoided, performance was best in the middle of the dark phase of the day and worst late in the light phase. The absence of a similar rhythm in the operant resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…(5) Although the aftereffects of shocks seem to have dissipated by the end of the 20-day shock phase, the anticipatory effect that appeared during the light phase was long lasting and was carried over into the to-day nonshock phase. The fact that the 21OO-h shocks had wide-ranging effects on consummatory behavior and general activity, both before and after the shock delivery ( Figures 5 and 6), is in sharp contast to Ghiselli and Patton's (1976) findings. They found that 2-h Sidman avoidance training had virtually no effect upon the general activity of rats during the remaining 22 h of the day, and that the nocturnal rhythm remained unaffected.…”
Section: Results For 2000-2100 Hoursmentioning
confidence: 77%
“…(5) Although the aftereffects of shocks seem to have dissipated by the end of the 20-day shock phase, the anticipatory effect that appeared during the light phase was long lasting and was carried over into the to-day nonshock phase. The fact that the 21OO-h shocks had wide-ranging effects on consummatory behavior and general activity, both before and after the shock delivery ( Figures 5 and 6), is in sharp contast to Ghiselli and Patton's (1976) findings. They found that 2-h Sidman avoidance training had virtually no effect upon the general activity of rats during the remaining 22 h of the day, and that the nocturnal rhythm remained unaffected.…”
Section: Results For 2000-2100 Hoursmentioning
confidence: 77%
“…Hamsters demonstrate enhanced T-maze alternation and novel object discrimination performance during and just before the dark phase (Ruby et al, 2008, 2013). These time of day differences are not observed in the acquisition of more complex operant conditioning tasks (Ghiselli & Patton, 1976; Stroebel, 1967) (c.f., (Mistlberger et al, 1996)). These latter findings suggest that the cognitive load of a task might overshadow changes from circadian timing, such that time-of-day modulation in acquisition may be more apparent on simpler tasks, but this hypothesis requires further investigation.…”
Section: Introductionmentioning
confidence: 90%
“…The performance of laboratory animals on a learning task varies with the phase of an LD cycle at which they are tested; such variations have been reported for conditioned suppression (Stroebel, 1967;Evans and Patton, 1970); avoidance learning (Davies, Navaratnam, and Redfern, 1973;Ghiselli and Patton, 1976;Gordon and Scheving, 1968); maze learning (Hostetter, 1966;Stavnes, 1972); and taste-aversion learning (Rusak and Zucker, 1974;Ternes, 1976). Daily rhythms might influence learning and performance in several ways; (1) variations in arousal, motivation (e.g., hunger), or sensory thresholds during acquisition and/or testing could modify the salience of discriminative cues as well as the value of rewards or punishments; (2) the ability to consolidate and store acquired information might vary with time of training; and (3) the ability to retain and recall stored information might vary with time of testing.…”
Section: Learning and Memorymentioning
confidence: 99%
“…In one study, performance efficiency, but not acquisition, was affected by time of day of testing (Ghiselli and Patton, 1976); in another, initial performance was equivalent among groups, but resistance to extinction varied dramatically with time of training (Ternes, 1976). Electroconvulsive shock (ECS) given to mice immediately after training disrupted memory equally well at two times of day, but ECS given 3 min after training disrupted memory only in mice tested during the D phase and not in those tested in L (Stephens, McGaugh, and Alpern, 1967).…”
Section: Learning and Memorymentioning
confidence: 99%